A Pilot Study to Teach Siblings to Support Children With Complex Communication Needs. (February 2018) - Douglas, Sarah N.; Kammes, Rebecca; Nordquist, Erica; D'Agostino, Sophia
Siblings play an important role in the lives of children with disabilities, especially those with complex communication needs (CCN). However, children with CCN require support to learn social and communication skills. Like other communication partners, typically developing (TD) siblings may struggle to understand how to best interact with a child with CCN and may benefit from training to learn communication strategies. This pilot study evaluated a newly created sibling communication partner training program to help TD siblings learn the strategy Plan, Talk, Wait, and Respond to support the communication of their siblings with CCN. A single-subject multiple probe design was used with three TD siblings and their siblings with CCN. Although results varied for sibling pairs, an increase in communication supports from TD siblings and communication gains for children with CCN were noted with all sibling pairs. Limitations, adjustments to the training, and future research directions are discussed.